2010
DOI: 10.1002/kin.20487
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of cyclic organic peroxides in pure solvents and binary solvent mixtures

Abstract: The thermal decomposition reaction of acetone cyclic triperoxide, acetone cyclic diperoxide, 4-heptanone cyclic diperoxide, and pinacolone cyclic diperoxide ca. 0.02 M was studied in pure solvents (acetone and 1-propanol) and in binary mixtures of acetone/1-propanol at 150 • C. The kinetics of each system was explored by gas chromatography (GC) at different solvent compositions. The reactions showed a behavior accordingly with a pseudo-first-order kinetic law up to at least 90% peroxide decomposition. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…substituents of the tetraoxacyclohexane ring in 7 clearly stabilizes the molecule, probably because it is confined in a compact solvent cage where the recyclization reaction is highly probable. Similar kinetic results have been obtained in previous works while studying the thermal decomposition in benzene, [15] toluene, [16] acetone, and propan-1-ol, [17] which demonstrates that 7 decomposes at the lowest rates in comparison with those cyclic peroxides with voluminous substituents (e.g., n-propyl, tertbutyl, and phenyl) (Table 4).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…substituents of the tetraoxacyclohexane ring in 7 clearly stabilizes the molecule, probably because it is confined in a compact solvent cage where the recyclization reaction is highly probable. Similar kinetic results have been obtained in previous works while studying the thermal decomposition in benzene, [15] toluene, [16] acetone, and propan-1-ol, [17] which demonstrates that 7 decomposes at the lowest rates in comparison with those cyclic peroxides with voluminous substituents (e.g., n-propyl, tertbutyl, and phenyl) (Table 4).…”
supporting
confidence: 88%
“…Diperoxide 6 has shown a very high reactivity not only in 1,4dioxan (Table 1) but in aprotic non-polar (toluene), [16] aprotic mildly polar (acetone), and protic solvents (propan-1-ol) (Table 4), [17] probably because of the presence of the bulky tert-butyl groups which causes a particular substituent effect on the rate constant values assigned to the O-O bond linkage. The thermal stability of 6 in solution appears close to that observed for voluminous trioxanes 1-3 rather than diperoxides 7 and 8 with similar van der Waals volumes (Fig.…”
mentioning
confidence: 99%
“…Regarding the kinetic and thermodynamic studies on the thermal decomposition of DEKTP and PDP in solution of solvents with different physicochemical properties Cañizo, 2006;Iglesias et al, 2010), the decomposition reactions obey a pseudofirst order kinetic law up to more than three half-lives for both peroxides, showing that there are no contributions from second order processes. Moreover, it was found that these cyclic peroxides thermally decomposed in solution by the homolytic cleavage of one of the O-O bonds generating a biradical intermediate (Scheme 2) which, in later stages, can be decompose following different routes Cañizo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1). 9,[12][13][14][15][16] It is very improbable that the biradical-activated complex would be solvated to the same extent as the starting material since differences in the electronic configuration, and therefore polarizability, should exist. The differential solvation of starting material and biradical--activated complex should lead to a difference in the reaction rate and subsequently in the activation parameter (e.g., energy of activation).…”
Section: Introductionmentioning
confidence: 99%